2022
DOI: 10.1051/0004-6361/202244064
|View full text |Cite
|
Sign up to set email alerts
|

Tidally induced spiral arm wraps encoded in phase space

Abstract: Context. The impact of Sagittarius and other satellite galaxies such as the Large Magellanic Cloud on our Galaxy and in particular its disc is gradually being disclosed. Simulations tailored to the interaction of the Milky Way (MW) and Sagittarius show rings and spiral arms appearing in the Galaxy disc. However, spiral arms can also be induced by the bar or by disc instabilities. Aims. We aim to study the dynamics of tidally induced spiral arms in the context of the different encounters with Sagittarius and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Based on two simulations in Khachaturyants et al (2022), one with warp caused by gas flowing into the Galactic disk and the other without warp, they found that the simulation with warp can produce a stronger bending wave. A better understanding of warp will promote the understanding of the kinematic structures and gas dynamics of the Galactic disk and Galactoseismology (Wang et al 2018a(Wang et al , 2018b(Wang et al , 2019(Wang et al , 2020a(Wang et al , 2020b(Wang et al , 2020cBland-Hawthorn & Tepper-Garcia 2021;Yu et al 2021;Wang et al 2023;Antoja et al 2022;Yang et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Based on two simulations in Khachaturyants et al (2022), one with warp caused by gas flowing into the Galactic disk and the other without warp, they found that the simulation with warp can produce a stronger bending wave. A better understanding of warp will promote the understanding of the kinematic structures and gas dynamics of the Galactic disk and Galactoseismology (Wang et al 2018a(Wang et al , 2018b(Wang et al , 2019(Wang et al , 2020a(Wang et al , 2020b(Wang et al , 2020cBland-Hawthorn & Tepper-Garcia 2021;Yu et al 2021;Wang et al 2023;Antoja et al 2022;Yang et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Using a toy model, Antoja et al (2018) found that the diagonal ridge structure could be generated by phase mixing from an out of equilibrium state corresponding to the perturbation from the pericentric passage of the Sagittarius dwarf galaxy (see also Antoja et al 2022), but which could also be strongly affected by the Galactic bar and/or spiral structure. Hunt et al (2018) found that a test particle model with winding spiral structure could reproduce the observed diagonal ridges well.…”
Section: Introductionmentioning
confidence: 99%